PENGEMBANGAN LEMBAR KEGIATAN SISWA YANG BERORIENTASI PADA PENEMUAN TERBIMBING DENGAN AZAS KONSTRUTIVISME PADA MATERI PLSV - Aries Suci Lestari (MEJ (Mathematics Education Journal), 2017)
The study is attempted to produce a teaching materials which students learning sheets that oriented by guided discovery learning done with valid, efficient, and effective constructivism principle as teaching materials. So with the made of this teaching materials expected to help students in understanding the material which being studied, in other words, students will getting better understanding for the learning concept. This research is kind of 3D development research which adapted from 4D development research including: define; design and; development. The data analysis was contained: validity analysis, practicalityanalysis, and effectiveness analysis.The result of this research indicated that validity aspect got the total average of 3,582 which categorized as valid .While on the practical aspect got the total average of 3,297 which categorized as well practical .Then on the effectiveness aspect divided from two aspect which are: student response which gets the total average of 3,229 which categorized as good and student exhaustiveness which 16 students was reaches the KKM and get percentage 72,727% that can be divined as effective.